PENGARUH PENYULUHAN TENTANG SISTEM INFORMASI POSYANDU (SIP) TERHADAP KETRAMPILAN KADER KESEHATAN - Dewi, Feti Kumala; Rini, Susilo (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Cadre activities undertaken in the Posyandu among other things prepare tools and materials, inviting and moving society, namely telling mothers to come to Posyandu, contact the working group (working group) Posyandu, namely submit plans for activities at the village office, filling and inform the Posyandu Information Systems. Based on interviews in District Kemangkon have never carry out counseling on how to fill Posyandu Information System, all the cadres know how to fill Posyandu Information System of self-taught midwife with posyandu. Objective: To analyze the Effect of Counseling About Posyandu Information System to the Skills of Health Cadre In District Kemangkon Purbalingga Year 2015. Type of research: research is the type of comparative analytical research with cross sectional method. Total population of 440 cadres, then sampling is done by cluster random sampling as many as 38 cadres. Instruments in this study using a checklist form integrated health information system and data were analyzed using the Wilcoxon test. Results: differences before the counseling skills of health cadres and skills of health cadres after counseling with p: 0.001 (<0.05), so there Extension Effect of Counseling About Posyandu Information System to the Skills of Health Cadre In District Kemangkon Purbalingga Year 2015. Keywords: Counseling, Posyandu Information System, Skills of Cadres